Grazing Intensity Impacts on Herbage Mass, Sward Structure, Greenhouse Gas Emissions, and Animal Performance: Analysis of Brachiaria Pastureland - Ruggieri, Ana Claudia [UNESP]; Cardoso, Abmael da Silva [UNESP]; Ongaratto, Fernando [UNESP]; Casagrande, Daniel Rume; Barbero, Rondineli Pavezzi; Brito, Liziane de Figueiredo [UNESP]; Azenha, Mariane Vieira; Oliveira, Andre Alves; Koscheck, Jefferson Fabiano Werner; Reis, Ricardo Andrade [UNESP] (Mdpi, 2020)
A 7 year experiment (2008-2014) evaluated cattle grazing intensity (sward height) effects on herbage mass, forage quality, and greenhouse gas emissions in continuously stocked pastures containing the tropical 'Marandu' palisade grass (Brachiaria brizantha (Hochst. ex A. Rich) Stapf cv. Marandu). The experiment consisted of three sward height treatments (15, 25, and 35 cm) and six replicates. There were four periods each year during the rearing phase. Significant effects were found for herbage mass, proportions of leaf and stem, crude protein, neutral detergent fiber, acid detergent fiber, lignin, animal performance, enteric methane (CH4), and greenhouse gas (GHG) emissions from soils. When the canopy height increased from 15 to 35 cm, the herbage mass rose from 5.23 to 9.86 kg t ha(-1), leaf percentage decreased, and stem percentage increased. Crude protein content averaged 14.2%, and neutral detergent fiber averaged 58%. Average daily gain averaged 0.67, 0.81, and 0.90 kg (-1) head(-1), while live weight gain ha(-1) was 649, 530, and 439 kg for the 15, 25, and 35 cm treatments, respectively. The weather variables explained the GHG emissions, interannual herbage mass, and structure variations.
Keywords: beef cattle; tropical pasture; Marandu grass; continuous stocking